Exosome proteomic analyses identify inflammatory phenotype and novel biomarkers in African American prostate cancer patients - Gati K. Panigrahi; Prakash P. Praharaj; Hiroki Kittaka; Asit R. Mridha; Olen M. Black; Rakesh Singh; Roger Mercer; Adrie van Bokhoven; Kathleen C. Torkko; Chapla Agarwal; Rajesh Agarwal; Zakaria Y. Abd Elmageed; et al. (Cancer Medicine)
Abstract African American men face a stark prostate cancer (PCa)‐related health disparity, with the highest incidence and mortality rates compared to other races. Additional and innovative measures are warranted to reduce this health disparity. Here, we focused on the identification of a novel serum exosome‐based “protein signature” for potential use in the early detection and better prognosis of PCa in African American men. Nanoparticle tracking analyses showed that compared to healthy individuals, exosome concentration (number/ml) was increased by ~3.2‐fold (P ˂ 0.05) in the sera of African American men with PCa. Mass spectrometry‐based proteomic analysis of serum exosomes identified seven unique and fifty‐five overlapping proteins (up‐ or downregulated) in African Americans with PCa compared to healthy African Americans. Furthermore, ingenuity pathway analyses identified the inflammatory acute‐phase response signaling as the top pathway associated with proteins loaded in exosomes from African American PCa patients. Interestingly, African American PCa E006AA‐hT cells secreted exosomes strongly induced a proinflammatory M2‐phenotype in macrophages and showed calcium response on sensory neurons, suggesting a neuroinflammatory response. Additionally, proteomic analyses showed that the protein Isoform 2 of Filamin A has higher loading (2.6‐fold) in exosomes from African Americans with PCa, but a lesser loading (0.6‐fold) was observed in exosomes from Caucasian men with PCa compared to race‐matched healthy individuals. Interestingly, TCGA and Taylor's dataset as well as IHC analyses of PCa tissue showed a lower Filamin A expression in tissues of PCa patients compared with normal subjects. Overall, these results support the usefulness of serum exosomes to noninvasively detect inflammatory phenotype and to discover novel biomarkers associated with PCa in African American men.